Forum Shopping under the EU Insolvency Regulation - Ringe, W (2008)
Cross-border forum shopping for a different insolvency law regime has become popular within the European Union in recent years. Yet legislators, courts and legal scholarship react with suspicion when debtors cross the border only to benefit from a different insolvency law system. The most prominent legal tool, the European Insolvency Regulation, is based on the assumption that forum shopping has a negative impact on the functioning of the European Internal Market. This paper questions the hostile attitude towards the phenomenon of forum shopping. It is argued that forum shopping can have beneficial effects both for the company and for its creditors, and that strong safeguards for creditors who oppose the migration are in place. Furthermore, the validity of the COMI approach of the Regulation under the fundamental freedoms of the Treaty is questioned; it is suggested that the current regime needs to be amended. The proposed new system would enable more corporate mobility within the European Union and create more legal certainty for all constituencies at the same time. © 2008 T.M.C.ASSER PRESS.